Identifying challenges in meeting the unmet health care needs of children with intellectual disabilities: a scoping review - Zahra Zare; Fatemeh Sarpourian; Faride Sadat Jalali; Mohammad Amin Bahrami (BMC Health Services Research)
Abstract Background Children with intellectual disability have significantly below-average intellectual functioning and adaptive behavior, experience more challenges in a lifetime, and are at higher risks of physical illness, mental health problems, and mortality compared to the unmet health care needs of others. Thus, this scoping review aimed to identify challenges in meeting the unmet healthcare needs of children with intellectual disabilities. Method This was a scoping review applying the JBI framework. Five databases of Scopus, PubMed, WOS, Embase, and ProQuest were systematically searched, applying related keywords up to 23.1.2024. All the retrieved studies in English, which determine the challenges in meeting the unmet healthcare needs of children with intellectual disabilities, were included regardless of their methodological designs. Microsoft Power BI was used for descriptive quantitative Analysis, and MAXQDA version 10 was applied for qualitative thematic Analysis. Results The number of 639 articles was retrieved systematically based on the search strategy. After excluding duplications and appraising the eligibility, 16 articles were included. According to the descriptive results, most studies were conducted in the US (37%). The results of the thematic Analysis also revealed six main themes: "Governance," "Care process," "Social challenges," “Information and education," "Infrastructure constraints," and “Personal challenges." Conclusion The findings comprehensively understand the challenges in meeting the unmet healthcare needs of children with intellectual disabilities. This synthesized knowledge could pave the way for policymakers to conduct related interventions better to improve unmet health care and, as a result, increase the children's health status.